Modeling Holonic Control Systems with IEC 61499 Subapplications and Applications - Vlad, V.; Graur, A.; Turcu, C. E.; Filote, C. (Elektronika ir Elektrotechnika, 2010)
Holonic control systems represent a relatively new paradigm, that carries out within manufacturing systems some principles and models, inspired from the manner in which living world systems are organized. The favorite technologies for designing such systems are mainly represented by the IEC standard for function blocks (61499) and by the multi-agent systems. A solution for modeling and implementing holonic control systems is proposed in this paper, based upon the use of ‘application’ and ‘subapplication’ concepts defined on IEC 61499 standard. The proposed solution is consistent with the HMS/FB function block based architecture, developed within “Holonic Manufacturing Systems” project.